Geothermics : heat flow in the lithosphere - Pasquale, Vincenzo; Verdoya, Massimo; Chiozzi, Paolo (Springer, 2017)
This book, now in its second edition, offers a comprehensive and modern treatment on the background knowledge of heat transfer processes in the lithosphere. In the light of the success of the first edition, several chapters of the book have been revised and the book has been enriched with a new chapter on geothermal methods used for the inference of past climate changes. The book starts with a brief review of global tectonics and of the structure of the crust and upper mantle. Then the theory of heat conduction as well as the thermal properties and the methods for the determination of thermal conductivity and radiogenic heat are introduced. Subsequently the geothermal flow and the thermal state of the lithosphere and deep interior are analyzed. The formation, upwelling mechanisms, solidification and cooling of magmas, which can be a fundamental heat source in many geothermal systems, are reviewed. Analytical methods used for gaining information on heat and groundwater flow from the analyses of temperature depth data are also covered. Data and practical examples are supplied to facilitate the understanding of the different topics. The book is intended for Earth science graduate students and researchers.
Keywords: Geodynamics.; Geothermal resources.; Lithosphere.; elektronické knihy; electronic books